Help is close at hand? Proximity and the effectiveness of peacekeepers. (October 2018) - Goldring, Edward; Hendricks, Michael
How do the national origins of peacekeepers influence peacekeeping operations' success? We argue that peacekeeping operations better protect civilians when a higher percentage of peacekeepers come from geographically proximate countries. These peacekeepers have been exposed to similar societal and cultural norms and are more invested in preventing conflict diffusion. Peacekeepers from proximate countries can better collect and analyze intelligence, are more effective at separating combatants, and are therefore more successful at protecting civilians. In making this argument, we also challenge the theory that diversity in a peacekeeping operation matters. We find support for both our mechanisms and show that the importance of diversity may have been overstated. Where a peacekeeping operation is present in civil conflicts, if a quarter of its personnel come from proximate countries, then all things being equal, it would completely prevent civilians dying. The results show policymakers the importance of recruiting peacekeepers from countries near to conflicts.